2019
DOI: 10.1155/2019/7982893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorine Ion on Metal Corrosion Behavior under the Scratch Defect of Coating

Abstract: The influence of chloride ion on the corrosion of metal under coating with scratch defects was researched by wire beam electrode (WBE) technology and electrochemical impedance spectroscopy (EIS) technology. The results showed that the current of metal surface could be characterized by the WBE technology. In the case of scratches on the coating, the location of the damage always showed an anodic current, and the cathodic reaction took place adjacent to the damaged location. The cathode area surrounded the defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…It was found that the corrosion rate was increased with the increment of Cl − . It can be attributed to the reason that the passivation film of steel can be damaged by chloride ions in the process of competing with hydrogen and oxygen ions in the absorption process, thus causing the occurrence of pitting corrosion [58].…”
Section: Effect Of the Average Chloridementioning
confidence: 99%
“…It was found that the corrosion rate was increased with the increment of Cl − . It can be attributed to the reason that the passivation film of steel can be damaged by chloride ions in the process of competing with hydrogen and oxygen ions in the absorption process, thus causing the occurrence of pitting corrosion [58].…”
Section: Effect Of the Average Chloridementioning
confidence: 99%
“…Tindak balas keluli seperti 316L dalam larutan yang mengandungi H2S dipengaruhi oleh faktor interaksi bahan (Zhang et al 2017), struktur mikro (Hashim et al 2019), saiz bahan (Aghuy et al 2015) dan juga faktor persekitaran yang merujuk kepada tekanan separa H2S ). Selain itu, kepekatan ion klorida (Cui et al 2019), pH , suhu (Handoko et al 2019), masa pendedahan (Melchers et al 2019) dan tekanan persekitaran (Nazarov et al 2019) turut mempengaruhi kelakuan kakisan keluli berkarbon rendah ini. Namun begitu, kajian kakisan yang melibatkan kesan gas H2S didapati masih di peringkat permulaan berbanding kajian kakisan yang berpunca daripada gas karbon dioksida (CO2) kerana kesukaran untuk bekerja di persekitaran yang mengandungi gas H2S ).…”
Section: Pendahuluanunclassified
“…This measure slowed the corrosion rate to a certain extent, but the corrosion problem still exists. In addition, if the anticorrosion layer has defects such as shedding, the corrosion rate of the buried pipeline will be further accelerated [3,[13][14][15]. According to investigations, sulfate reducing bacteria, iron bacteria, iron oxidizing bacteria, and sulfur oxidizing bacteria have a great influence on metal corrosion, and SRB is considered to be one of the most influential microorganisms [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%